1973
DOI: 10.1038/bjc.1973.144
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Reaction in Trophoblastic Tumours

Abstract: Summary.-The presence of a mononuclear cell reaction to 41 gestational choriocarcinomata, 10 invasive moles and 13 malignant trophoblastic teratomata has been investigated. The intensity of the reaction was graded; there was a significantly better response to therapy and survival rate in those with a " severe " cellular reaction than in those with a " mild " reaction to gestational choriocarcinoma. The pathological and clinical features of invasive moles showed no relationship with the cellular reaction to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

1976
1976
1988
1988

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…This has been reported in breast cancer (4), choriocarcinoma (5), neuroblastoma (6), and melanoma (7), among others. Also, macrophage phagocytosis of melanoma cells has been reported (8).…”
Section: Introductionmentioning
confidence: 55%
“…This has been reported in breast cancer (4), choriocarcinoma (5), neuroblastoma (6), and melanoma (7), among others. Also, macrophage phagocytosis of melanoma cells has been reported (8).…”
Section: Introductionmentioning
confidence: 55%
“…It has been suggested that the infiltration of mononuclear cells in gestational choriocarcinoma is a response to tumour antigens (Elston and Bagshawe, 1973). Such a reaction could also reflect the histocompatibility differences between tumour and host, since the evidence presented in this paper favours the idea that trophoblastic tumours express HLA specificities.…”
Section: Cellular Reactionmentioning
confidence: 63%
“…Elston and Bagshawe [9] reported that an infiltrate of mononuclear cells in trophoblastic tumors was probably a response to the presence of tumor antigens. In this study, however, the amount of TIL recovered was greater in patients without recurrence than in those with recurrence within 2 years after complete resection.…”
Section: Discussionmentioning
confidence: 99%